Authenticate yourself once using OpenID - Katuk, Norliza; Koo, Lee Chun; Zakaria, Nur Haryani; Mohamad Tahir, Hatim; Halim, Mohamad Subri (Dynamic Publishers Inc., USA, 2015)
This paper presents a research concerning users' behaviours towards Web Single-Sign-On (SSO) for accessing e-learning applications.Many web application providers require users to subscribe to their services and authenticate themselves through the use of login credentials. The number of such applications is increasing exponentially which caused ineffective login credentials management among users.This may also contribute to various security issues to both users and application providers.Web SSO, a type of authentication service has been introduced to overcome the issues pertaining password management.However, the utilization of web SSO for accessing educational materials is still at its infancy stage; where many aspects of the technology has not been fully studied and developed.Hence, there is a need to study how users of e-learning applications behave towards web SSO. A course portal named CWS was developed with two authentication methods (i.e., OpenID and traditional). A focus group interview and a laboratory experiment were conducted on students from two higher learning institutions.The aim of these studies is to understand how students behave towards the authentication methods.The results of the study reveal important findings on users' behaviours towards web SSO implementation particularly OpenID.The outcomes are further discussed in terms of applicability of web SSO within e-learning environment.